THE PHANTOM MENACE. - WISE, DAVID (Smithsonian, 2015)
The article discusses Soviet Union's uncovering of double agent spies in the Soviet KGB (Komitet gosudarstvennoi bezopasnosti) intelligence service who were secretly working for the U.S. Central Intelligence Agency and the British intelligence service MI6 during 1985, including double agents Oleg Gordievsky, Colonel Sergei Ivanovich Bokhan and Andrei Poleshchuk. The impact that the Soviet arrest of CIA Soviet counterintelligence division Aldrich Ames had on the uncovering of double agents is discussed.